The Impact of Visual Frameworks on Teacher Candidates’ Professional Reflection (LEARNing Landscapes, 2011)
This study examined teacher candidates’ reflections about the use of two graphic organizers referenced in their teacher education program. Fourteen themes were identified relating to teacher candidates’ instructional focus; awareness of the value of the organizers to improve focus on their students’ learning, growth, and independence with instructional tasks; and their focus on professional growth. Data from this study provides information to allow future comparison of teacher candidates’ diversity in reflections with their teaching evaluations. Connections with brain development are identified to support the use of complex graphic organizers in professional contexts for teachers.
Keywords: reflection; teacher; graphic organizer; learning; growth; independence; teaching evaluation; brain development; professional context